Evaluation of the learning curve in terms of operation time in robotic assisted unicondylar knee arthroplasty (Annals of Medical Research, 2022)
Aim: There are few studies in the literature evaluating the robotic assisted unicondylar knee arthroplasty (rUKA) learning curve. This study aimed to evaluate the learning curve in robotic assisted unicondylar knee arthroplasty in terms of operation time.Materials and Methods: The data of patients who underwent rUKA between October 2016 and December 2019 were retrospectively analyzed. Age, gender, side, and body mass index (BMI) values of the patients were obtained from the patient files. To compare the operation times, the patients were divided into two groups. The first group represented patients who had surgery in the first half of the follow-up period (n=27), while the last group represented patients who had surgery in the second half of the follow-up period (n=28).Results: During the study period, rUKA was performed on 55 patients (42 females, 13 males) with a mean age of 64.1 years. The demographic data of the two groups were similar. The mean operative times of the first (n=27) and the last groups (n=28) were 101.8±16.1 minutes, and 84.8±9.9 minutes, respectively (p
Keywords: Robotic assisted; Osteoarthritis; Medial compartment; Arthroplasty; Unicondylar